A Lattice Boltzmann and Immersed Boundary Scheme for Model Blood Flow in Constricted Pipes: Part 2 – Pulsatile Flow (Communications in Computational Physics, 2014)
One viable approach to the study of haemodynamics is to numerically modelthis flow behavior in normal and stenosed arteries. The blood is either treated as Newtonianor non-Newtonian fluid and the flow is assumed to be pulsating, while thearteries can be modeled by constricted tubes with rigid or elastic wall. Such a task involvesformulation and development of a numerical method that could at least handlepulsating flow of Newtonian and non-Newtonian fluid through tubes with and withoutconstrictions where the boundary is assumed to be inelastic or elastic. As a firstattempt, the present paper explores and develops a time-accurate finite difference latticeBoltzmann method (FDLBM) equipped with an immersed boundary (IB) schemeto simulate pulsating flow in constricted tube with rigid walls at different Reynoldsnumbers. The unsteady flow simulations using a time-accurate FDLBM/IB numericalscheme is validated against theoretical solutions and other known numerical data. Inthe process, the performance of the time-accurate FDLBM/IB for a model blood flowproblem and the ease with which the no-slip boundary condition can be correctly implementedis successfully demonstrated.